The slow death of capital protection - Christian Bauer; Marc Oliver Rieger (Journal of Risk and Financial Management, 2021)
Capital protected products are a special type of structured retail products that guarantee a minimum amount of payment at maturity. They were the earliest type of structured products and are very popular with risk averse investors, but nevertheless have become rare in the past years. Using a unique dataset of all structured products issued in Switzerland, one of the biggest markets for such products in the world, we investigate why this has been the case, and argue that it is to a large degree an effect of the zero-interest policy of central banks.
Keywords: 330; capital protected notes; guarantee certificates; loss aversion; structured financial products; structured notes; structured products; zero interest policy